1995
DOI: 10.1002/1098-108x(199503)17:2<105::aid-eat2260170202>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Family interactions in bulimia nervosa I: Study design, comparisons to established population norms, and changes over the course of an intensive day hospital treatment program

Abstract: This paper presents the results of a study examining self‐reported family functioning by patients with bulimia nervosa (BN) and their parents before and after treatment for the eating symptoms of BN. Ratings of family functioning improved significantly over the course of treatment. There was no evidence of excessive denial or social desirability in the families. © 1995 by John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 25 publications
0
18
2
1
Order By: Relevance
“…Previous studies that found differences in perception of family functioning among family members, either using the FAD (13) or the Family Assessment Measure (14) did not indicate what factors were underlying these differences. Daughters perceive the family functioning as more pathologic than do their mothers.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies that found differences in perception of family functioning among family members, either using the FAD (13) or the Family Assessment Measure (14) did not indicate what factors were underlying these differences. Daughters perceive the family functioning as more pathologic than do their mothers.…”
Section: Discussionmentioning
confidence: 82%
“…The results of the FES and the PBI could also potentially index predisposing factors, although responses to these items could also be affected by later psychiatric status (Woodside et al, 1995). Reporting on family environment, the affected twins recalled their families as having more discord.…”
Section: Discussionmentioning
confidence: 99%
“…The methods employed in this study have been described in Part I of this paper (Woodside et al, 1995). Briefly, a measure of family functioning, the Family Assessment Measure (FAM; Skinner, Steinhauer, & Santa-Barbara, 1983) was administered to families of individuals attending an intensive day hospital program for eating disorders.…”
Section: Methodsmentioning
confidence: 99%